PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS SPARKOL VIDEOSCRIBE YANG DIINTEGRASIKAN DENGAN WONDERSHARE FILMORA PADA MATA PELAJARAN GEOGRAFI MATERI MITIGASI BENCANA ALAM - Yunita Bouato; Fitryane Lihawa; Rusiyah Rusiyah (Universitas Negeri Gorontalo, 2020)
Development of Learning Media based on Sparkol VideoScribe Integrated with Wondershare Filmora on Geography Subject with Material of Natural Disaster Mitigation. This research aims to know the development of learning media based on Sparkol VideoScribe integrated with Wondershare Filmora on geography subject with material of natural disaster mitigation. This research applies Research and Development (R and D) method developed by Borg and Gall and adapted to the needs of the researcher. Data collection was conducted using observation, interview, questionnaire, and documentation in which the instrument used in the form of assessment criteria to know the feasibility of the media from the material expert, media expert, and geography teachers as well as students' responses on the learning media by using questionnaires. The collected data is research finding regarding the quality of learning media and suggestions for product revisions. The results of the validation of the material expert, media expert and the geography teacher obtained an average rating of 94.90% which is classified into